German culture in nineteenth-century America : reception, adaptation, transformation - Tatlock, Lynne, 1950-; Erlin, Matt (Studies in German literature, linguistics, and culture., 2005)
Building on recent trends in the humanities and especially on scholarship done under the rubric of cultural transfer, this volume emphasizes the processes by which Americans took up, responded to, and transformed German cultural material for their own purposes. The fourteen essays by scholars from the US and Germany treat such topics as translation, the reading of German literature in America, the adaptation of German ideas and educational ideals, the reception and transformation of European genres of writing, and the status of the "German" and the "European" in celebrations of American culture and criticisms of American racism. The volume contributes to the ongoing re-conception of American culture as significantly informed by non-English-speaking European cultures. It also participates in the efforts of historians and literary scholars to re-theorize the construction of national cultures. Questions regarding hybridity, cultural agency, and strategies of acculturation have long been at the center of postcolonial studies, but as this volume demonstrates, these phenomena are not merely operative in encounters between colonizers and colonized: they are also fundamental to the early American reception and appropriation of German cultural materials